Differential hydrogen/deuterium exchange mass spectrometry analysis of protein––ligand interactions. (February 2011) - Chalmers, Michael J; Busby, Scott A; Pascal, Bruce D; West, Graham M; Griffin, Patrick R
Functional regulation of ligand-activated receptors is driven by alterations in the conformational dynamics of the protein upon ligand binding. Differential hydrogen/deuterium exchange (HDX) coupled with mass spectrometry has emerged as a rapid and sensitive approach for characterization of perturbations in conformational dynamics of proteins following ligand binding. While this technique is sensitive to detecting ligand interactions and alterations in receptor dynamics, it also can provide important mechanistic insights into ligand regulation. For example, HDX has been used to determine a novel mechanism of ligand activation of the nuclear receptor peroxisome proliferator activated receptor-γγ, perform detailed analyses of binding modes of ligands within the ligand-binding pocket of two estrogen receptor isoforms, providing insight into selectivity, and helped classify different types of estrogen receptor-αα ligands by correlating their pharmacology with the way they interact with the receptor based solely on hierarchical clustering of receptor HDX signatures. Beyond small-molecule––receptor interactions, this technique has also been applied to study protein––protein complexes, such as mapping antibody––antigen interactions. In this article, we summarize the current state of the differential HDX approaches and the future outlook. We summarize how HDX analysis of protein––ligand interactions has had an impact on biology and drug discovery.